Enhancing critical and creative thinking through English oral presentations in online learning: a conceptual exploration / Majdah Chulan, Mohamad Fadhili Yahaya and Latisha Asmaak Shafie - Chulan, Majdah; Yahaya, Mohamad Fadhili; Shafie, Latisha Asmaak (Universiti Teknologi MARA, Kedah, 2025)
The purpose of this conceptual paper is to highlight the effectiveness of English oral presentation for enhancing the university students’ critical thinking skills and creativity in online learning. Critical thinking and creativity are among the two most important skills demanded among the university students, particularly during English oral presentations in classroom. Students may find the task challenging because they are required to initially read, research, plan, write and finally present ideas creatively and critically in English. They must be creative when producing their ideas, and support them critically with logical explanations, details, and examples in front of their friends and lecturers. However, when Covid-19 pandemic occurred, face-to-face and online learning were the approaches for students to learn and educators to teach. The implementation of e-learning in teaching and learning process could be a way to realize this goal where technological tools usage has provided new opportunities to enhance the students’ critical thinking and creativity in delivering their English oral presentation. Thus, an in-depth literature review was conducted within the realm of both thinking skills in relation to students’ oral presentation. In addition, a conceptual framework which connects the relationship between the educators’ feedback and digital tools used to develop, stimulate, and engage students’ critical thinking and creativity is proposed for further exploration. This study contributes to the current literature on both thinking skills and its effectiveness on the university students’ English oral presentation while emphasising the need for more research in this area.